2020
DOI: 10.3389/fmicb.2020.01585
|View full text |Cite
|
Sign up to set email alerts
|

A Unique B-Family DNA Polymerase Facilitating Error-Prone DNA Damage Tolerance in Crenarchaeota

Abstract: Sulfolobus islandicus codes for four DNA polymerases: three are of the B-family (Dpo1, Dpo2, and Dpo3), and one is of the Y-family (Dpo4). Western analysis revealed that among the four polymerases, only Dpo2 exhibited DNA damage-inducible expression. To investigate how these DNA polymerases could contribute to DNA damage tolerance in S. islandicus, we conducted genetic analysis of their encoding genes in this archaeon. Plasmid-borne gene expression revealed that Dpo2 increases cell survival upon DNA damage at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 73 publications
1
32
0
Order By: Relevance
“…On the other hand, Lundgren and Bernander (2007) suggested that the PolB1 of S. acidocaldarius performs both leading- and lagging-strand syntheses based on the temporal patterns of transcription of all four polymerases with respect to the cell-division cycle. More recently, biochemical properties of the B-family polymerases of Sulfolobus and related genera have been investigated, and argue that the PolB1 enzymes play this replicative role ( Choi et al, 2011 ; Bauer et al, 2012 ; Peng et al, 2016 ; Yan et al, 2017 ), and this conclusion is supported by functional genetic criteria in S. acidocaldarius (this study) and closely related crenarchaea ( Feng et al, 2020 ). The recent evidence that Sulfodiicoccus acidiphilus , a member of the order Sulfolobales lacks PolB3 ( Sakai and Kurosawa, 2019 ) also strongly supports a replicative role of PolB1.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…On the other hand, Lundgren and Bernander (2007) suggested that the PolB1 of S. acidocaldarius performs both leading- and lagging-strand syntheses based on the temporal patterns of transcription of all four polymerases with respect to the cell-division cycle. More recently, biochemical properties of the B-family polymerases of Sulfolobus and related genera have been investigated, and argue that the PolB1 enzymes play this replicative role ( Choi et al, 2011 ; Bauer et al, 2012 ; Peng et al, 2016 ; Yan et al, 2017 ), and this conclusion is supported by functional genetic criteria in S. acidocaldarius (this study) and closely related crenarchaea ( Feng et al, 2020 ). The recent evidence that Sulfodiicoccus acidiphilus , a member of the order Sulfolobales lacks PolB3 ( Sakai and Kurosawa, 2019 ) also strongly supports a replicative role of PolB1.…”
Section: Discussionmentioning
confidence: 66%
“…A contribution of TLS in the survival of bulky lesions has been suggested by in vitro studies in which S. solfataricus Dpo4 bypassed benzyl adducts, whereas the PolB2 and PolB3 enzymes of S. solfataricus did not ( Choi et al, 2011 ; see Table 1 ), and in which Dpo4 replicated past cisplatin lesions ( Boudsocq et al, 2001 ). The PolB2 polymerases are distinct from the other DNAPs of Sulfolobales in being induced by UV ( Fröls et al, 2007 ; Götz et al, 2007 ; Feng et al, 2020 ). In addition, phenotypic analyses indicate that the PolB2 of a strain related to S. solfataricus increases survival of UV-C, cisplatin, and NQNO ( Feng et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations